STRATEGI ANSHAR AKIL CHANNEL DALAM PEMBUATAN KONTEN PEMBELAJARAN DI YOUTUBE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The focus of this research is to find out Anshar Akil Channel's strategy in creating content on YouTube and find Anshar Akil Channel's tips for maintaining the quality of learning content in the face of competition for similar content on YouTube. Using a qualitative approach, this research uses a character study model focusing on the Anshar Akil Channel strategy in creating learning content on YouTube. The data collection methods are through observation, in-depth interviews, and documentation. Data analysis was carried out in four stages: data classification, data reduction, data description, and conclusions. The results of this research show that Anshar Akil Channel's first problem formulation did not carry out large-scale research, only reading books or journals if there was new material that had not been mastered because Anshar Akil had worked as a lecturer for 16 years so the course material was taught. have mastered a lot. Anhsar Akil Channel uses today's technology and designs learning content that is simple without much variation so that the points conveyed can be conveyed directly. Anshar Akil Channel specializes in targeting students only for educational purposes. To improve the quality of content, Anshar Akil always learns new things about YouTube and continues to hone his skills. The second problem formulation shows that Anhsar Akil always learns new things to maintain the quality of content and always analyzes similar content so that the resulting content remains relevant. Anshar Akil always carries out personal branding so that the audience knows more about the Anshar Akil Channel YouTube account and always provides feedback to the audience to increase engagement.